Stories of young dropouts: a social survey of success and failure - Mateus, S. (ICERI2021 - 14th annual International Conference of Education, Research and Innovation, 2021)
This presentation discusses the results of a qualitative research on causes and processes of early school leaving, conducted in 2017 in 8 European cities (Amadora/Portugal, Northampton/United Kingdom, Paris/France, Genova and Cuneo/Italy, Osijek and Djal/Croatia, Bucharest/Romania). The research objectives were: a) to give voice to young people's experiences and the process, causes and effects of early school leaving, retention and dropping out; b) to gather a number of "typical histories" of early school leaving or risks of dropping out that reflect the different situations in which ESL occurs; c) to identify the complex factors, actions, and views underlying ESL not only at individual level but also at school and community levels. The following research questions were address empirically: at local level, what are the factors causing school failure, early school leaving and dropping out? How can ESL and dropping out be reduced? Involving young people and conducting a more critical research process led to young people taking on the role of experts as participants. Around 290 young people who have dropped out of school early, or at risk of dropping out, were involved in focus groups and interviews. As experts, the young people outlined solutions and offered insights into the research topic, simultaneously highlighting the systemic nature of early school leaving and the complex processes that mark the school trajectory and biography of students up to and beyond the moment of dropping out. Results show that early school leaving is a complex, multi-dimensional phenomenon with numerous causes and consequences. The diversity and complexity of the youngsters’ trajectories reveal that a large group of factors are involved in the production of failure (as well as of success). The inclusion of different countries has made it possible to identify common factors and experiences, despite the different educational systems, levels of social development, or school organization.